Filosofi Pendidikan Islam Dalam Perspektif Al-Qur`an - miskahuddin bin yahya lizam (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Education is the main thing that the Qur'an talks about. The first verse revealed by Allah to His Prophet is Surah Al-`Alaq Verses One to Five which is essentially important to read with Bismirabbik. The values of education can be of good quality if humans try to continuously learn to improve their quality by reading, studying, writing and researching in the main things that provide wisdom with deep and healthy knowledge. Education can always be directed to exploring self-potential which refers to his approach to Allah SWT, the Creator of all the universe. Reading here is in the scope of deep and active meaning such as mentadabbur, studying and researching in depth, observing, analyzing, such as existing natural objects, discussing, writing books and the scope of other scientific activities that can use sharp thinking and reasoning for means worship Allah SWT. The Qur'an also talks about wise education to humans which is enshrined in it the virtues of teaching and Lukmanul Hakim's education to his favorite child so that he can gain wisdom in his life and teaching with the right method for the education of his children and for mankind on this earth. .